Cheylostigmaeus tarae sp. nov. and Stigmaeus delaramae sp. nov. (Acari: Stigmaeidae) from Kurdistan, Iran - Khanjani, Mohammad; Nasrollahi, Siamak; Zamani, Ali Sina; Fayaz, Bahman Asali (Zootaxa, 2014)
Two new species belonging to the family Stigmaeidae, Cheylostigmaeus tarae sp. nov. and Stigmaeus delaramae sp. nov., are described from specimens collected from soil and litter under pear trees, Pyrus communis L. (Rosaceae) in Iran. A key to all Iranian species of the genera Cheylostigmaeus (male) and Stigmaeus (female) are provided.